Competitive advantage and organisational performance in selected firms - Christian, Ogala Sunday (International research journal of management, IT and social sciences, 2020)
This study examined competitive advantage and organizational performance in, Delta State. A 12-item validated structured questionnaire served as the research instrument to 125 staff and customers of the selected firms in Delta State. Two objectives and hypotheses to examine the impact of resource availability on organizational performance and to determine the effect of research and development performance guided the study. The major analytical tools used were correlation and multiple regression analysis. Primary data was used on a sample of 125 members of staff. It was found that there is a strong relationship between Resource availability, Research and development, and firm performance. The researcher, therefore, concluded that Resource availability positively affects the firm strategic performance in the firms selected. Bringing together expertise and capabilities from various organizations improves the performance of a product. Combining financial resources and strategic alliances help in improving the performance of a product. The strategic resources, however, which are generally intangible, are neither easily identifiable nor rapidly developed. Hence, the researcher recommends that there is a need for management of these manufacturing firms to enhance their Resource availability as this will lead to organization performance.